Trends in Trade Credit Insurance in Poland - Becella, Adrian (Studia Oeconomica Posnaniensia, 2015)
This article presents the problem of the development of trade credit insurance in Poland. The development is determined by various factors. The author focuses on the cyclicality of economies, which affects the degree of companies' access to insurance coverage. The impact of economic fluctuations on the trade credit insurance market in Poland was recognised in 2008, when after a few years of dynamic development barriers appeared which limited the effectiveness of the described instrument. The aim of this study is to define possible solutions in terms of developing insurance products which could more adequately meet market expectations. One solution in the insurance of liabilities is the use of a security system established by the debtor for the benefit of the creditor or even the insurance company. The models presented, with additional insurance protection, improve the security of the financial entity and the creditor while at the same time increasing the efficiency of their operations. Moreover, they improve the liquidity of the debtor due to the limits on commercial transactions. To conclude, in the opinion of the author the insurance of liabilities supported by an additional security system constitutes a positive response for some creditors to deteriorating economic conditions on the market. It increases the importance of the product and at the same time creates foundations for its further development.